Pemanfaatan Media Power Point Untuk Meningkatkan Minat Belajar Bahasa Inggris Siswa Kelas VIII SMP N 21 Kerinci - Jeni Alida (Jurnal Pendidikan Islam, 2021)
This research employs a class action of 2 cycles in grade VIII SMP Negeri 21 Kerinci with a total of 22 students. The data is collected using student interestquestionnaires, observation sheets and interviews. The results found that there was an increase in interest in learning English from SMP Negeri 21 Kerinci students by utilizing power point media. The increase can be seen from the average result of student interest in pre cycles being at 22.8, in cycle I increasing to 27, 23, until cycle II increased to 35.11. To sum up, the media power point can increase the interest of learning English students of the State Junior High School 21 Kerinci after achieving the indicator of success that wants to be achieved that is in cycle II